(untitled) (Bangladesh Journal of Botany, 2026)
Ten endophytic fungi were isolated from the leaves and stems of Gynura procumbens (Lour.) Merr. The identification of all the fungi was carried out up to the genus level based on colony morphology and microscopic characteristics. Seven of these fungi were further identified at the species level, namely: Muyocopron laterale, Ectophoma multirostrata, Nemania abortiva, Diaporthe rosae, Colletotrichum aciculare, Fusarium perseae, and N. feicuiensis, utilizing BLAST analysis of the amplified sequences of the internal transcribed spacer (ITS) region. This study marks the first report of these fungi as endophytes of G. procumbens in Bangladesh. This study also performed a biochemical assessment on ethyl acetate extracts from the isolated endophytic fungi, including antimicrobial, antioxidant, and thin-layer chromatography (TLC). Most of the crude extracts from the fungi exhibited one or more biological activities. TLC analysis revealed a variety of phytochemical components, such as flavonoids, terpenoids, anthraquinones, coumarins, isocoumarins, and steroids in all isolates. These results imply that the endophytic fungi associated with G. procumbens could serve as a valuable source for investigating potential bioactive compounds or as starting points for developing new drugs. Bangladesh J. Bot. 55(1): 123-132, 2026 (March)